Pengaruh Pemberian Omeprazole Terhadap Profil Farmakokinetika Piroxicam Dengan Metode Kromatografi Cair Kinerja Tinggi (KCKT) - Dasma Arihan Nauli Sipayung (Jurnal Penelitian Farmasi & Herbal, 2022)
Piroxicam is an anti-inflammatory drug belonging to the NSAID group and is also used as an analgesic and anti-rheumatic drug. Its use is often combined with stomach medicines, as the side effects of piroxicam can irritate the stomach. One of them is omeprazole. Since piroxicam and omeprazole act on the same enzyme, CYP450, they can affect the pharmacokinetic profile, especially at the metabolic stage and excretion of piroxicam. The purpose of this study was to determine the effect of omeprazole on the pharmacokinetic profile of piroxicam especially in the metabolic phase and excretion. The method used in this study was an experimental method using three male rabbits. These rabbits are divided into three groups. The first treatment group was giving pyroxicam solution 0.653 mg / kg body weight, the second treatment group gave piroxicam 0.653 mg / kg body weight that one hour before was given omeprazole 1.2 mg / kg body weight and the third group treated with piroxicam 0.7 mg / kg body weight at the same time with omeprazole 1,4 mg / kg body weight. Plasma levels of the drug piroxicam are measured using a high performance liquid chromatography (HPLC) tool. The verification method is executed. This is the determination of LOD and LOQ values, accuracy and accuracy testing. The result of data analysis using t-table. The results showed that there was an increase or difference in pharmacokinetic parameter values ​​during the absorption phase, but no significant effect was shown for each group. Pharmacokinetic parameter values ​​for metabolic stages and excretion were reduced and no significant difference was shown between the groups. Simultaneous administration of omeprazole and piroxicam and administration of piroxicam 1 hour before omeprazole may inhibit piroxicam-metabolizing enzymes and thus affect pharmacokinetic parameters and excretion during absorption, but are not significant.